Anak di Luar Kawin dalam Hukum Kewarisan Islam: Sebuah Ragam Perspektif dan Analisa - Meidina, Ahmad Rezy; Misbachussurur (Jurnal Syariah dan Hukum Komparatif, 2022)
Indonesian people commit a lot of fornication and not a few people get pregnant out of legal marriage. Not only that case, but we also find many people in Indonesia who practice unregistered marriages. These cases from both practices have causes and effects on the status of children, which is in the context of inheritance, both Islamically and legally in Indonesia. Therefore, regarding the child's status, it is necessary to ask what the status of his inheritance is. The author uses library research methods or literature studies to answer these questions. In this case, the results of this research will be found from various literature and perspectives to resolve the status of children out of marriage with a broader explanation. From the author's search, it was found that children who birth from fornication (out of Islamic marriage) did not get a share of the inheritance. Meanwhile, the status of a child from an unregistered marriage also does not get an inheritance as long as it cannot be adequately proven.